Peran Sistem Pengendalian Manajemen dalam Mendukung Circular Economy Sebagai Bentuk Kontribusi Perusahaan dalam Pelestarian Lingkungan pada Cita Entertainment - Kintania Juaayunata; Ida Bagus Ketut Bayangkara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the role of the management control system in supporting Circular Economy standards at Event Organizer CV Cita Entertainment. This research method uses a qualitative method with a descriptive analysis approach. Results show that the scope of this research includes budget planning, logistics and evaluation processes. And the items used are items that are not disposable and can be reused for further activities, in accordance with the 3R concept (Reduce, Reuse, Recycle). Planning and budgeting of goods is carried out carefully so that the circular economy concept can be realized and aims to save the budget. Waste processing procedures that focus on the reuse of durable goods. This is achieved by recording and updating data regarding items that can be used repeatedly. This way, they don't end up as trash, contributing to overall waste minimization. This research aims to provide an understanding of the application of Circular Economy principles in industrial management activities through an effective management control system and targeted waste processing procedures